2019
DOI: 10.3390/ijms20102518
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response (UPR) in Survival, Dormancy, Immunosuppression, Metastasis, and Treatments of Cancer Cells

Abstract: The endoplasmic reticulum (ER) has diverse functions, and especially misfolded protein modification is in the focus of this review paper. With a highly regulatory mechanism, called unfolded protein response (UPR), it protects cells from the accumulation of misfolded proteins. Nevertheless, not only does UPR modify improper proteins, but it also degrades proteins that are unable to recover. Three pathways of UPR, namely PERK, IRE-1, and ATF6, have a significant role in regulating stress-induced physiological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 121 publications
1
70
0
Order By: Relevance
“…Our results showed that the Annexin/PI phenotype was also coupled with the over-expression of many apoptotic proteins when (a) GSK2606414-treated cells were compared with non-treated cells, as well as when (b) GSK2606414/BTZ-treated cells were compared to BTZ-treated cells. Given the dual function of PERK both in cell survival and apoptosis [ 15 , 45 ], we sought to determine whether GGSK2606414 on its own or, more interestingly, in combination with BTZ, would drive cells to increased apoptosis and hence sensitize cells to more effective combination therapies. Among the apoptotic proteins upregulated, survivin has been previously described as being associated with ER stress and UPR gene expression in colonic epithelial cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the Annexin/PI phenotype was also coupled with the over-expression of many apoptotic proteins when (a) GSK2606414-treated cells were compared with non-treated cells, as well as when (b) GSK2606414/BTZ-treated cells were compared to BTZ-treated cells. Given the dual function of PERK both in cell survival and apoptosis [ 15 , 45 ], we sought to determine whether GGSK2606414 on its own or, more interestingly, in combination with BTZ, would drive cells to increased apoptosis and hence sensitize cells to more effective combination therapies. Among the apoptotic proteins upregulated, survivin has been previously described as being associated with ER stress and UPR gene expression in colonic epithelial cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A robust UPR induction, causes lethal ER stress. 38 However, a moderate induction of that pathway has been associated with protective responses in the endothelium. 39 In particular, the transfection of human pulmonary artery endothelial cells with siRNA for BiP (the ER Hsp70) promoted the filamentous actin formation and abrogated endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the addition of a phenyl group, PBA acquires also the capacity to act as chemical chaperone and may consequently help to restore the proper conformation of unfolded proteins, whose accumulation induces ER stress. ER stress/Unfolded Protein Response (UPR), usually activated in the cancer cells due to the intrinsic or extrinsic insults, may sustain cancer survival/chemoresistance [1]. Both PBA and NaB are histone deacetylase inhibitors (HDACis), and as such, they may hold a strong anti-cancer potential [2], also at sublethal doses.…”
Section: Introductionmentioning
confidence: 99%